Parental Leave, (In)formal Childcare and Long-term Child Outcomes - Natalia Danzer; Martin Halla; Nicole Schneeweis; Martina Zweimüller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
There is a strong debate about who should provide care to young children. Governments offer two alternative types of institutions: formal childcare and parental leave. We assess the effectiveness of these two competing institutions in promoting child development by comparing how a major parental leave extension from one to two years affected Austrian children's long-term outcomes in communities with and without formal childcare facilities for under-3-year-olds. Empirical identification of treatment effects is based on a sharp birthday cutoff-based discontinuity in the eligibility for extended parental leave and geographical variation in formal childcare. We find evidence that the counterfactual mode of care is decisive. If formal childcare is available, the reform induced a replacement of formal childcare by maternal care and had zero (or negative effects) on child outcomes. Whereas if formal childcare is not available, informal childcare was replaced by maternal care, and the reform improved child outcomes. This heterogeneity is driven by the additional time with the mother in the second year of the child's life and not by a change in maternal income. We conclude that care provided by mothers or formal institutions is superior to informal care-arrangements.
Keywords: J13; H52; J22; J12; I38; 330; Parental leave; formal childcare; informal childcare; child development; maternal labor supply; fertility